Tracheostomy timing and outcome in critically ill patients with stroke: a meta-analysis and meta-regression - Premraj, Lavienraj; Camarda, Christopher; White, Nicole; Godoy, Daniel Agustin; Cuthbertson, Brian H.; Rocco, Patricia R. M.; Pelosi, Paolo; Robba, Chiara; Suarez, Jose I.; Cho, Sung-Min; Battaglini, Denise (Critical care (London, England), 2023)
Background Stroke patients requiring mechanical ventilation often have a poor prognosis. The optimal timing of tracheostomy and its impact on mortality in stroke patients remains uncertain. We performed a systematic review and meta-analysis of tracheostomy timing and its association with reported all-cause overall mortality. Secondary outcomes were the effect of tracheostomy timing on neurological outcome (modified Rankin Scale, mRS), hospital length of stay (LOS), and intensive care unit (ICU) LOS. Methods We searched 5 databases for entries related to acute stroke and tracheostomy from inception to 25 November 2022. We adhered to PRISMA guidance for reporting systematic reviews and meta-analyses. Selected studies included (1) ICU-admitted patients who had stroke (either acute ischaemic stroke, AIS or intracerebral haemorrhage, ICH) and received a tracheostomy (with known timing) during their stay and (2) > 20 tracheotomised. Studies primarily reporting sub-arachnoid haemorrhage (SAH) were excluded. Where this was not possible, adjusted meta-analysis and meta-regression with study-level moderators were performed. Tracheostomy timing was analysed continuously and categorically, where early (< 5 days from initiation of mechanical ventilation to tracheostomy) and late (> 10 days) timing was defined per the protocol of SETPOINT2, the largest and most recent randomised controlled trial on tracheostomy timing in stroke patients. Results Thirteen studies involving 17,346 patients (mean age = 59.8 years, female 44%) met the inclusion criteria. ICH, AIS, and SAH comprised 83%, 12%, and 5% of known strokes, respectively. The mean time to tracheostomy was 9.7 days. Overall reported all-cause mortality (adjusted for follow-up) was 15.7%. One in five patients had good neurological outcome (mRS 0–3; median follow-up duration was 180 days). Overall, patients were ventilated for approximately 12 days and had an ICU LOS of 16 days and a hospital LOS of 28 days. A meta-regression analysis using tracheostomy time as a continuous variable showed no statistically significant association between tracheostomy timing and mortality ( β = − 0.3, 95% CI = − 2.3 to 1.74, p = 0.8). Early tracheostomy conferred no mortality benefit when compared to late tracheostomy (7.8% vs. 16.4%, p = 0.7). Tracheostomy timing was not associated with secondary outcomes (good neurological outcome, ICU LOS and hospital LOS). Conclusions In this meta-analysis of over 17,000 critically ill stroke patients, the timing of tracheostomy was not associated with mortality, neurological outcomes, or ICU/hospital LOS. Trial registration : PROSPERO—CRD42022351732 registered on 17th of August 2022.